A systematic review of local vulnerability to climate change: in search of transparency, coherence and comparability - Delaney, A.; Chesterman, Sabrina; Crane, Todd A.; Tamás, Peter A.; Ericksen, Polly J. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Because vulnerability is a conceptual construct rather than a directly observable phenomenon, most vulnerability assessments measure a set of “vulnerability indicators”. In order to identify the core approaches and range of variation in the field, we conducted a systematic literature review on local vulnerability to climate change. The systematic review entailed an identification of frameworks, concepts, and operationalizations and a transparency assessment of their reporting. Three fully defined relevant frameworks of vulnerability were identified: IPCC, Patterns of Smallholder Vulnerability and Vulnerability as Expected Poverty. Comparative analysis found substantial heterogeneity in frameworks, concepts and operationalizations, making it impossible to identify patterns of climate vulnerability indicators and determinants that have robust empirical support. If research measuring farmers’ vulnerability to climate change is to have any comparability, it needs greater conceptual coherence and empirical validity. We recommend a systematic program of testing and validating vulnerability measures before institutionalizing them in programmatic contexts.